(untitled) (Historia, 2021)
Alfred Milner appeared frigid to many who encountered him, though his close friends and the young men known as the "kindergarten" basked in his personal warmth and charm, as did the women in his life. Biographers may also have been chilled by the "imperial icicle", as someone at the Cape called him and he has received so little close attention that J. Lee Thompson's new biography of him is called Forgotten Patriot.